2011
DOI: 10.1038/jid.2010.272
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling after Lipid Raft Disruption in Keratinocytes Identifies Critical Mediators of Atopic Dermatitis Pathways

Abstract: Lipid rafts are cholesterol-rich cell signaling platforms, and their physiological role can be explored by cholesterol depletion. To characterize transcriptional changes ongoing after lipid raft disruption in epidermal keratinocytes, a cell type that synthesizes its cholesterol in situ, we performed whole-genome expression profiling. Microarray results show that over 3,000 genes are differentially regulated. In particular, IL-8, urokinase-like plasminogen activator receptor, and metalloproteinases are highly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 50 publications
1
40
1
2
Order By: Relevance
“…Therefore m␤cd is suitable for detecting false positive cholesterol protein interactions in DRM studies (14 -19). Proteins depleted on m␤cd treatment are finally considered to be sterol dependent (15)(16)(17). To compare the m␤cd treatment for disturbing the sterol distribution in the L o fraction, we studied the sterol biosynthesis deficient mutant smt1.…”
mentioning
confidence: 99%
“…Therefore m␤cd is suitable for detecting false positive cholesterol protein interactions in DRM studies (14 -19). Proteins depleted on m␤cd treatment are finally considered to be sterol dependent (15)(16)(17). To compare the m␤cd treatment for disturbing the sterol distribution in the L o fraction, we studied the sterol biosynthesis deficient mutant smt1.…”
mentioning
confidence: 99%
“…Filaggrin -2 expression is even more downregulated than that of pro -fi laggrin in lipid raftdisrupted keratinocytes, a situation that is described as resemblance of AD concerning its transcriptional profi le [ 68 ]. At the protein level, a downregulation has been observed in nonlesional and even more in lesional skin samples of AD patients [ 64 ].…”
Section: Filaggrin-2: the Functional Relationmentioning
confidence: 96%
“…17 What is interesting is that patients with genetic differences tend to be susceptible to both this condition and other related allergic diseases. 24,25 Such large-scale genome profiling and genetic experiments have confirmed that the disruption of lipid rafts can lead to inflammatory disease under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis has even been shown to occur in parallel with keratinocytes disrupted by lipid rafts. 17 We hypothesize that inflammatory diseases of the airway are influenced by airway epithelial cells with disrupted lipid rafts, similar to keratinocytes in atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation